2020
DOI: 10.1177/1073191120954914
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Distress Tolerance and Neighboring Emotion Regulation Abilities

Abstract: Distress tolerance has fuzzy boundaries with neighboring emotion regulation abilities. In the present study, we probed the structure of this domain and examined its link to emotional disorder outcomes. We recruited mental health patient ( ns = 225 and 210) and university student ( n = 1,525) samples to report on diverse components of distress tolerance, emotion dysregulation, experiential avoidance, and anxiety sensitivity. Confirmatory factor analysis supported a one-factor model of these individual differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
3
26
0
Order By: Relevance
“…Clinically speaking, the existence of many disorder-specific interventions (i.e., single-disorder protocols [SDPs]) places additional burden on clinicians to learn and administer different SDPs, contributing to clinician burnout and preventing patients from receiving care that they need (Kazdin, 2008;Kazdin & Blase, 2016;McHugh & Barlow, 2010). Recently, researchers have begun to more comprehensively investigate the degree to which aversive reactivity constructs relate to neuroticism (Naragon-Gainey & Watson, 2018), to one another (Conway et al, 2020;Spinhoven et al, 2017), and to other related constructs such as emotion dysregulation (Conway et al, 2020;Juarascio et al, 2020). From a clinical perspective, empirical efforts to compare transdiagnostic cognitive-behavioral interventions (i.e., the Unified Protocol [UP]) to disorder-specific protocols demonstrated that the UP resulted in equivalent symptom reduction, suggesting equal effectiveness with less attrition and less clinician burden (Barlow et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically speaking, the existence of many disorder-specific interventions (i.e., single-disorder protocols [SDPs]) places additional burden on clinicians to learn and administer different SDPs, contributing to clinician burnout and preventing patients from receiving care that they need (Kazdin, 2008;Kazdin & Blase, 2016;McHugh & Barlow, 2010). Recently, researchers have begun to more comprehensively investigate the degree to which aversive reactivity constructs relate to neuroticism (Naragon-Gainey & Watson, 2018), to one another (Conway et al, 2020;Spinhoven et al, 2017), and to other related constructs such as emotion dysregulation (Conway et al, 2020;Juarascio et al, 2020). From a clinical perspective, empirical efforts to compare transdiagnostic cognitive-behavioral interventions (i.e., the Unified Protocol [UP]) to disorder-specific protocols demonstrated that the UP resulted in equivalent symptom reduction, suggesting equal effectiveness with less attrition and less clinician burden (Barlow et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although emotion dysregulation is an important and related process, and others have explored its overlap with constructs representing aversive reactivity (e.g., Conway et al, 2020), we chose to exclude it from our review. Emotion dysregulation research is characterized by a broad literature with inconsistent definitions of this construct; some (e.g., Trull et al, 2015;Linehan, 1993) view emotion dysregulation more akin to neuroticism (frequent, intensive, unstable emotions) whereas others (e.g., Gross et al, 2011) consider this construct to reflect ability to modulate emotional responses.…”
Section: Componentsmentioning
confidence: 99%
“…Like AS, individuals with elevated standing on DI hold inflexible views of emotional distress as aversive, see themselves as unable to regulate their emotions, and become reluctant to experience distressing emotions (Clen et al, 2011). As seen in these definitions, AS and DI share some features and may be best conceptualized as facets of a global affect intolerance dimension (Conway et al, 2020; Juarascio et al, 2020). However, important distinctions exist between the two constructs, with anxiety-related interoceptive and somatic sensations at the core of AS, but not DI (Zvolensky et al, 2011).…”
Section: Anxiety Sensitivity and Distress Intolerancementioning
confidence: 99%
“…Distress tolerance refers to the ability to experience and withstand aversive psychological states without engaging in efforts to avoid or eliminate these states (Simons & Gaher, 2005), and appears to be part of a broader dimension (including emotion dysregulation, anxiety sensitivity, and experiential avoidance) reflecting individual differences in responses to negative emotional states (Conway et al, 2020). Difficulty tolerating distress (i.e., distress intolerance) is suggested to contribute to the development and maintenance of a range of different forms of psychopathology and problem behaviors (Leyro et al, 2010).…”
Section: Distress Intolerancementioning
confidence: 99%